Determination of Ionospheric Parameters over Iraqi Zone - Aziz, Aqeel; Hadi, Khalid (Iraqi Journal of Science, 2024)
In this paper, an analytical study for the behavior of ionospheric parameters (Maximum Usable Frequency (MUF) and Optimum Traffic Frequency (FOT)) has been preformed between transmitter station (Baghdad) and many different receiver stations which are distributed randomly over Iraqi territory. The ionospheric parameters dataset has been made using ICEPAC communication model for annual time for the years 2009-2011 of the solar cycle 24. A simplified ionospheric model has been suggested which based on the correlated relationship between the geographical locations coordinates (longitudes & latitudes) of receiver stations and the dataset of the MUF and FOT parameters. The results of this study showed that the correlation between the ionospheric parameters and geographical location coordinates can be expressed as linear surface equation. The predicated ionospheric parameters values using the suggested empirical model show a good fitting with theoretical values that calculated using the international models.